Assessment of indoor air quality (IAQ): a review - Mohamed Sunar, Norshuhaila; Parjo, Umi Kalthsom; Subramaniam, Menega; Leman, Abdul Mutalib (Penerbit UTHM, 2020)
The assessment of IAQ is carried out by routine activity that includes some of the factor that related to the indoor environment. The factor such as the sources of indoor air contaminants, environmental tobacco smoke, air contaminants, either from indoor or outdoor sources and the sufficiency of mechanical ventilation. All of this assessment should include as the required measurement of the specific physical parameters and indoor air contaminants. The walkthrough inspection involved such as identified the potential contaminants and sources, carried out the available information about the history ventilation system in the building and collected the previous record of IAQ complaints [1]. Here there are some parameters to indicate IAQ status whether comfortable and healthy environmental to the building’s occupant. The parameter includes physical, chemical, biological and ventilation performance indicator conditions in a building that affect the health, comfort, and performance of occupants that further explain in these topics. The specific physical parameters consist of air temperature, relative humidity and air movements based on Industry Code of Practice (ICOP-IAQ), Department Occupational Safety and Health [1]. The performance indicator, carbon dioxide was measured...